Unravelling the versatile feeding and metabolic strategies of the cold-water ecosystem engineer Spongosorites coralliophaga (Stephens, 1915). (November 2018) - Kazanidis, Georgios; van Oevelen, Dick; Veuger, Bart; Witte, Ursula F.M.
Abstract: Sponges are often major players in the functioning of shallow-water ecosystems through their high biomass and high capacity in filter feeding. In comparison, little is known about the feeding and metabolic strategies of deep-sea sponges, although they can also form dense aggregations with high biomass. This situation hinders our understanding about how some sponge species thrive under the often food-limited conditions of the deep sea. In the present study we examined the feeding and metabolic strategies of 1) the massive demosponge Spongosorites coralliophaga, which was recently described as an important ecosystem engineer in cold-water coral reefs (CWCRs) and 2) the anthozoan Parazoanthus anguicomus and the ophiuroid Ophiura ophiura, i.e. two dominant epibionts on S. coralliophaga . All three benthic species have high density at CWCRs of the North-East Atlantic and knowing their feeding strategies facilitates future studies on carbon (C) and nitrogen (N) cycling at CWCRs. The on-board feeding experiments examined the processing of four isotopically-labelled food sources, namely 15 N-ammonium chloride, 13 C-glucose, 13 C/ 15 N-labelled microalgae, 13 C/ 15 N-labelled bacteria by S. coralliophaga and its symbiotic bacteria and the epibionts P. anguicomus and O. ophiura from the Mingulay reef complex and the Logachev mound (North-East Atlantic). There were no significant differences among the three species in terms of biomass-specific C and N assimilation rates; however, there were differences among S. coralliophaga, P. anguicomus and O. ophiura in how they processed the food sources and this maybe is linked to interspecific variability in metabolic needs. S. coralliophaga preferentially assimilated particulate organic N (PON) over particulate organic C (POC) while this was not the case for P. anguicomus and O. ophiura . We did not detect the 15 N tracer in the bacterial biomarkerD -Alanine suggesting that the preferential assimilation of N over C in S. coralliophaga was mediated by sponge cells instead of the bacterial symbionts. S. coralliophaga assimilated C and N from all four food sources and this versatile feeding strategy was accompanied by an ability for de novo synthesis of essential and non-essential hydrolysable amino acids (HAAs). We suggest that the recorded feeding and metabolic flexibility of S. coralliophaga plays an important role in the survival of this massive sponge under food-limited conditions in the deep sea. Highlights: Cold-water ecosystem engineer sponge feeds on dissolved and particulate sources. Preferential assimilation of nitrogen over carbon was not mediated by symbiotic bacteria. Build-up of essential amino acids from inorganic compounds by the sponge holobiont.